The nature, consequences, mechanisms, and management of sleep disturbances in individuals at-risk for psychosis - Fekih-Romdhane, Feten; Hallit, Souheil; Cheour, Majda; Jahrami, Haitham (Frontiers in Psychiatry, 2022)
There is strong evidence that sleep disturbances are commonly experienced by people with psychosis. Evidence has also shown that sleep disturbances are present since the very early stages of the disease, even during the pre-diagnostic phase. More recently, research involving young individuals at ultra-high risk (UHR) for psychosis documented frequent occurrence of sleep disturbances in this group. The very early onset of sleep disturbances in the course of psychosis has drawn attention to the possible links between sleep parameters and the risk of psychosis. To date, the nature of sleep disturbances characterizing the UHR stage remains unclear, with available studies having yielded mixed findings. In this regard, we performed this review to update the body of literature on the nature of sleep disturbances, their underlying mechanisms, their clinical and functional consequences, the prevention and intervention strategies in the at-risk for psychosis population. Our findings provided further support to the presence of disturbed sleep in UHR individuals as evidenced by subjective and objective sleep measures such as polysomnography, sleep electroencephalograms, and actigraphy. Reviewing the possible mechanisms underlying the relationship between sleep and psychosis emphasized its complex and multifactorial nature which is yet to be determined and understood. Further research is warranted to determine which facets of sleep disturbances are most detrimental to this specific population, and to what extent they can be causal factors or markers of psychosis.